Determinants of Tax Avoidance Practices: Fundamental Analysis Approach and Company Size in LQ 45 Companies for the Period 2020-2024 - Upessy, Veska Maria Christin; Pascalina, Pascalina V. S. Sesa; Salle, Hesty T.; Allolayuk, Theo; Antoh, Alfiana; Tandililing, Elia M.; Wonar, Klara (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine and analyze the influence of Return on Assets, Debt to Equity Ratio, Price to Book Value, and Company Size on Tax Avoidance. The data used in this study are secondary, sourced from company fact sheets from the Indonesia Stock Exchange (IDX) and company financial reports. The population in this study uses companies included in the LQ45 index during the 2020-2024 period. The research sample used was obtained through purposive sampling. The data analysis technique used was panel data regression in EViews 12. The study's results indicate that Return on Assets, Debt to Equity Ratio, Price to Book Value, and Company Size do not significantly affect Tax Avoidance.